Feeding ecology of a selective folivore, the thin-spined porcupine (Chaetomys subspinosus) in the Atlantic forest - Fernandez Gine, Gaston Andres; Barbanti Duarte, Jose Mauricio; Faria, Deborah (Alliance Communications Group Division Allen Press, 2010)
We studied the feeding ecology of the thin-spined porcupine (Chaetomys subspinosus), a small arboreal rodent endemic to the Atlantic rain forest of Brazil and threatened with extinction. We captured and radiotracked 4 free-ranging individuals and collected 1,177 feeding records in 944 h of observation between April 2005 and September 2006. We found that the animal feeds exclusively on the leaves of woody trees, preferring young leaves. Diet composition and foraging pattern did not vary seasonally, although we observed a seasonal variation in the availability of young leaves. Annual diet comprised primarily (90%) 4 plant species, Albizia pedicellaris, Inga thibaudiana, Pera glabrata, and Tapirira guianensis. This small subset of plant species contains high levels of both leaf protein and fiber, and most preferred species have the capacity to establish symbiotic associations with nitrogen-fixing bacteria. A diet concentrated in a few taxonomically related, nitrogen-fixing species suggests that in addition to high protein levels other features linked to chemical tolerance and local abundance of food items also influence the use and selection of food by this small browser. We conclude that C. subspinosus is more folivorous than previously thought and that it is highly selective in food choice, as expected for a small arboreal mammalian folivore. Because the animals selected pioneers species that are locally abundant, widespread, and typical of early secondary forests, we suggest that food supply is not a limiting factor for the presence of thin-spined porcupines in small disturbed forest patches in the Atlantic forest. DOI: 10.1644/09-MAMM-A-185.1.
Keywords: arboreal folivores; Atlantic Rainforest; diet; feeding ecology; folivory; porcupine; Seasonality; Selectivity